1999
DOI: 10.12935/jvma1951.52.231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Applied Ozonated Autohemotherapy on Ananastasia and Dysstasia in Dairy Cows

Abstract: SUMMARYOzonated autohemotherapy was applied to 27 cows with incurable ananastasia and dysstasia due to arthritis, laminitis, post dystocic neuroparalysis and Downer syndrome. Seventeen of 27 (63%) treated cows recovered showing obvious lentitive effect and smooth standing action as well as significantly decreased levels of serum GOT and CPK activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the present study, a decline in the CD4 + /CD8 + ratio was observed after OAHA. A significant decrease in the CD4 + /CD8 + ratio with ozone exposure was reported [13,19]. It has been suggested that these responses may be due to activation of a Th2 cell dependent response that in turn leads to a downregulation of Th1 mediated immunity.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In the present study, a decline in the CD4 + /CD8 + ratio was observed after OAHA. A significant decrease in the CD4 + /CD8 + ratio with ozone exposure was reported [13,19]. It has been suggested that these responses may be due to activation of a Th2 cell dependent response that in turn leads to a downregulation of Th1 mediated immunity.…”
mentioning
confidence: 94%
“…Recently, it was reported that OAHT also had a favorable effect in cows with incurable ananastasia and dysstasia [13]. In OAHT for cows with disease, we have to know the mechanism of the various effects by ozonated autohemoadministration (OAHA).…”
mentioning
confidence: 99%